2022
DOI: 10.1097/mpg.0000000000003600
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Functional Constipation and Growth Status: A Systematic Review and Meta-Analysis

Abstract: Objectives: Functional constipation (FC) and malnutrition are 2 of the most common diseases affecting children worldwide with long-term consequences. We hereby performed a systematic review and meta-analysis to analyze the relationship between these 2 entities. Methods: We searched PubMed, American Academics of Pediatrics (AAP), Cochrane, ClinicalTrials.gov (from inception to December 11, 2021) using “constipation,” “growth,” and “children” as the keywords. Newcastle-Ottawa Scale was used as the risk of bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, this report is controversial, as other studies have reported on the correlation between chronic constipation and overweight and obesity (Koppen et al, 2016;Olaru et al, 2016;Santos-Andreoli et al, 2019). A recent systematic review and meta-analysis which evaluated eighteen studies involving 33,410 children reported that childhood constipation is associated with the prevalence of overweight and obesity (Lazarus et al, 2022). Children with constipation also demonstrated higher somatic scores when compared to healthy children (Appak et al, 2017;Kilincaslan et al, 2014;Rajindrajith et al, 2013).…”
Section: Amendments From Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this report is controversial, as other studies have reported on the correlation between chronic constipation and overweight and obesity (Koppen et al, 2016;Olaru et al, 2016;Santos-Andreoli et al, 2019). A recent systematic review and meta-analysis which evaluated eighteen studies involving 33,410 children reported that childhood constipation is associated with the prevalence of overweight and obesity (Lazarus et al, 2022). Children with constipation also demonstrated higher somatic scores when compared to healthy children (Appak et al, 2017;Kilincaslan et al, 2014;Rajindrajith et al, 2013).…”
Section: Amendments From Versionmentioning
confidence: 99%
“…However, other studies revealed the possible association between FC and excessive body weight. Second, a more recent systematic review and meta-analysis (Lazarus et al, 2022) evaluated eighteen studies involving 33,410 children and concluded that FC correlates with the prevalence of overweight and obesity. Ref-2, 3…”
Section: Abstract Clearly Describedmentioning
confidence: 99%
“…A metaanalysis of 18 studies involving 33,410 children showed a statistically significant relationship between functional constipation and both overweight and obesity (OR = 1.75). 3 Furthermore, a recently published meta-analysis has confirmed the significant association between obesity and constipation in children in developed countries. 4 Interestingly, it seems that in developing countries children do not have an higher risk of having constipation if they are obese; however, the reason for this geographical difference is not yet clear.…”
mentioning
confidence: 90%
“…While awaiting such evidence, we want to point out that only one third of obese patients with FGIDs seek medical attention for their symptoms. 3 Therefore, we also think that pediatricians should pay more attention to the gastrointestinal symptoms present in children with an increased BMI.…”
mentioning
confidence: 99%